Men who have sex with men is the high‐risk drug resistance population: A meta‐analysis of HIV‐1 drug resistance profiles and trends in China. (18th September 2022) - Yuan, Defu; Liu, Yangyang; Zhou, Ying; Shi, Lingen; Chen, Jianshuang; Lu, Jing; Fu, Gengfeng; Wang, Bei
Abstract: What is Known and Objective: Except for the transmitted drug resistance (TDR)'s standard sampling and monitoring protocol, China's HIV‐1 pretreatment drug resistance (PDR) and acquired drug resistance (ADR) results vary widely due to the studies' diverse background. This meta‐analysis was conducted to comprehensively understand the drug resistance profiles of Chinese HIV/AIDS patients and compare the drug resistance differences among groups to provide a reference for the further improvement of treatment protocols. Methods: Data sources for this study were WANFANG, VIP, CNKI, SinoMed, PubMed and Web of Science databases from January 1, 2010 to January 13, 2022. Data extracted from the literature were analyzed by R and Stata to evaluate the profile and changing trend of drug resistance in Chinese HIV/AIDS patients. Results and Discussion: One hundred twenty‐one literature were included. The combined PDR and ADR in the Chinese HIV/AIDS patients was 5.56% (95% CI: 4.77%–6.41%) and 51.33% (95% CI: 47.57%–55.38%), respectively. The time trend analysis shows the upward trend of PDR. There were significate differences in ADR among different sample sources, the ADR in the central region were higher than those in all other regions. The PDR in men who have sex with men (MSM) was lower the whole population, while the MSM's ADR was much higher than whole population. What is New and Conclusion: PDR in China showed an upward trend and exceeded the 5% warning line but is still at a low level worldwide. ADR is stable and below the middle level globally; the comprehensively promoted free ART in China still has lasting effects. MSM is the high‐risk drug resistance population, targeted treatment strategies should be used. Abstract : We searched WANFANG, VIP, CNKI, SinoMed, Pubmed, and Web of Science databases to conduct a meta‐analysis that strictly checked the definition of drug resistance rate to comprehensively understand the drug resistance profiles of Chinese HIV/AIDS patients. Furthermore, found that the acquired drug resistance incidence in the men who have sex with men (MSM) population was much higher by comparing the increased extent of drug resistance between MSM and the whole population.